2018
DOI: 10.1002/elan.201800497
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical Determination of Vancomycin at a Graphene‐modified Electrode: Comparison of Electrochemical Property between Graphene, Carbon Nanotube, and Carbon Black

Abstract: Carbon nanotube, graphene and carbon black, as electrode modifiers, were compared and evaluated for the electrochemical determination of vancomycin. Among them, the best results were obtained at the graphene‐modified electrode. Additions of vancomycin using square wave voltammetry at the graphene‐modified electrode showed a linear range from 0.70 μM to 50 μM and a detection limit of 0.20 μM was obtained. To control the correct dose of vancomycin and reduce its side effects, its accurate determination in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Also, graphene has special properties which make it an interesting working surface in electrochemistry. This direction was also supported by previously reported data [9], which showed that graphene is a more sensitive electrochemical platform for VAN detection and by other data present in the literature [10]. The further improvement of graphene as a sensing platform by modifying it with AuNSs was considered and tested.…”
Section: Electrochemical Studiessupporting
confidence: 74%
See 2 more Smart Citations
“…Also, graphene has special properties which make it an interesting working surface in electrochemistry. This direction was also supported by previously reported data [9], which showed that graphene is a more sensitive electrochemical platform for VAN detection and by other data present in the literature [10]. The further improvement of graphene as a sensing platform by modifying it with AuNSs was considered and tested.…”
Section: Electrochemical Studiessupporting
confidence: 74%
“…In this regard, the direct electrochemical detection of VAN was recently reported [9,10]. Considering its large molecule and the need of analysis from complex matrices, a more complex approach for the direct electrochemical detection, involving the development and use of a complex electrochemical fingerprint of VAN, was recently reported [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroanalytical determination of Vancomycin at a graphene-modified electrode using square wave voltammetry was developed for the determination of Vancomycin in human plasma [107] .…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…Modification of electrodes with various modifiers is very important for improving quality of sensors for drugs analysis with low sensitivity . In recent years, different types of nanomaterials such as metal oxide nanostructures have been applied as modifiers in sensors .…”
Section: Introductionmentioning
confidence: 99%